Imidazolyl MOF material as well as preparation method and application thereof

By preparing imidazolyl MOF materials with brick-like morphology and layered crystal structure, the problem of insufficient morphology and size of existing MOF materials is solved, and the apparent activity of electrolytic water reaction is improved. The process is gentle, green and simple. .

CN119306959APending Publication Date: 2025-01-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310859676.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing MOF materials have fewer morphology and size, making it difficult to accurately regulate through gentle and green methods, limiting their performance improvement in electrochemical applications.

Method used

Using an imidazolyl MOF material with brick-like morphology and layered crystal structure, a rapid ion adsorption or exchange capability is prepared by reacting a specific proportion of surfactant and organic ligand with metal source precursors. MOF material and use it as a self-forming panel to construct a stable brick-like hollow structure, which is used in electrolytic water reaction.

Benefits of technology

It improves the apparent activity of electrolytic water reaction, has simple process, mild conditions, green and environmentally friendly, and is suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306959A_ABST
    Figure CN119306959A_ABST
Patent Text Reader

Abstract

The invention relates to the field of preparation of MOF materials, and particularly discloses an imidazolyl MOF material as well as a preparation method and application thereof. The invention relates to an imidazolyl MOF (Metal Organic Framework) material. The MOF material has a brick-like shape; the MOF material has a layered crystal structure. The imidazolyl MOF material is applied to a water electrolysis reaction, and the apparent activity of the water electrolysis reaction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of MOF materials, and in particular to an imidazole-based MOF material and a preparation method and application thereof. Background Art

[0002] With the continuous development of human society, energy and environmental problems are becoming increasingly severe, so there is an urgent need to develop clean, renewable green new energy, such as wind energy, solar energy, nuclear energy and hydrogen energy. In order to better develop and utilize these new energy sources, it is necessary to develop corresponding new energy storage and conversion devices, such as new lithium-ion batteries, lithium-sulfur batteries, supercapacitors, fuel cells and water electrolysis devices. Importantly, one of the key links is the research and development of high-performance new materials.

[0003] Generally speaking, the electrochemical performance can be improved by micronizing the electrode materials and rationally designing their composition and structure, optimizing the morphology and electronic structure of the materials. Design and synthesize some novel micro-nano structures, such as doped carbon composite structures, hollow nanostructures, multi-metal uniform doping, and three-dimensional hierarchical structures. One of the important strategies to achieve the above synthesis is to use metal-organic frameworks (MOFs) materials as self-templates for subsequent related synthesis designs, especially the synthesis of micro-nano-sized MOF materials with special morphologies, which can build multi-level structures on this basis and further improve the electrochemical performance.

[0004] Studies have shown that MOF materials are periodically coordinated crystalline materials formed by self-assembly of transition metal ions and organic ligands. They have many advantages such as high porosity, large specific surface area, regular pores, adjustable pore size, and topological structure diversity, and can be used as one of the ideal self-template materials. At present, the morphology and size of MOF are still relatively small. For example, imidazole-based ligands are usually rhombic dodecahedrons, cubes, rods, and sheets. MOF materials with new morphologies and sizes are still worthy of further exploration. Micro-nano materials derived from MOF are usually closely related to the structure and composition of MOF materials (precursors). Therefore, how to accurately regulate the composition and morphology of MOF materials through mild and green methods is also one of the important challenges in this field. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide an imidazole-based MOF material and a preparation method and application thereof. The imidazole-based MOF material is applied to the electrolysis of water reaction, which is beneficial to improving the apparent activity of the electrolysis of water reaction.

[0006] In order to achieve the above objectives, the present invention provides an imidazole-based MOF material on one hand, wherein the MOF material has a brick-like morphology; the MOF material has a layered crystal structure.

[0007] Preferably, the size of the MOF material is (6-16)×(2-5)×(0.6-2.5) μm.

[0008] A second aspect of the present invention provides a method for preparing a MOF material, the method comprising the following steps: (1) reacting an aqueous solution containing a surfactant and an organic ligand with an aqueous solution of a metal source precursor to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The mass dosage ratio of the organic ligand, the metal source precursor and the surfactant is 0.9-1.3:1:0.05-0.4.

[0009] The third aspect of the present invention provides an application of the imidazole-based MOF material described in the first aspect or the imidazole-based MOF material prepared by the method described in the second aspect in a water electrolysis reaction.

[0010] Through the above technical solution, the beneficial effects of the present invention include: The MOF material of the present invention has a brick-like morphology and a layered crystal structure, and ion adsorption or exchange is relatively fast. At the same time, it is convenient to use it as a self-template to subsequently construct a stable brick-like hollow structure, and is applied to the electrolysis of water reaction, which is beneficial to improve the apparent activity of the electrolysis of water reaction. Preferably, the imidazole-based MOF material has a suitable three-dimensional space size of micro-nano scale, and is applied to the electrolysis of water reaction, which is further beneficial to improve the apparent activity of the electrolysis of water reaction.

[0011] The present invention adopts a one-step reaction method to obtain the MOF material of the present invention, which has simple process, mild conditions, is green and environmentally friendly, and is suitable for wide application. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a SEM image of the MOF material prepared in Example 1 of the present invention; Figure 2 is the XRD pattern of the MOF material prepared in Example 1 of the present invention; Figure 3 is a SEM image of the MOF material prepared in Comparative Example 2 of the present invention; Figure 4 is a SEM image of the MOF material prepared in Comparative Example 3 of the present invention; Figure 5 is a SEM image of the MOF material prepared in Comparative Example 4 of the present invention; Figure 6It is a SEM picture of the MOF material prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0014] One aspect of the present invention provides an imidazole-based MOF material, wherein the MOF material has a brick-like morphology; the MOF material has a layered crystal structure.

[0015] In the present invention, the MOF material having a brick-like morphology means that the MOF material has a morphology similar to a rectangular parallelepiped, and the side surfaces consisting of the length and height are slightly convex curved surfaces.

[0016] The brick-like morphology of the MOF material of the present invention is measured by SEM.

[0017] The layered crystal structure of the MOF material of the present invention is measured by XRD, which can be referred to Figure 2 .from Figure 2 It can also be seen that the MOF material also has high crystallinity.

[0018] The MOF materials in the prior art are usually in the form of rhombic dodecahedrons, cubes, rods or sheets, and have problems such as slow ion exchange rate and unstable structure, which leads to significant damage in subsequent reactions. The MOF material with a brick-like morphology and a layered crystal structure described in the present invention has relatively fast ion adsorption or exchange, and can be used as a self-template to facilitate the subsequent construction of a stable brick-like hollow structure. It is applied to water electrolysis reaction, which is beneficial to improving the apparent activity of the water electrolysis reaction.

[0019] According to the present invention, preferably, the size of the MOF material is (6-16)×(2-5)×(0.6-2.5) μm, preferably (8-15)×(2.5-4.5)×(0.8-2.2) μm. The use of MOF materials of this preferred size in subsequent water electrolysis reactions is more conducive to improving the apparent activity of the water electrolysis reaction.

[0020] In the present invention, the size of the MOF material is expressed as length×width×height.

[0021] The size of the MOF material of the present invention is measured by SEM.

[0022] According to the present invention, preferably, the metal element in the MOF material is zinc and / or cobalt. This preferred embodiment can better coordinate with the organic ligand molecule of the present invention.

[0023] The organic ligand of the present invention can be a conventional choice in the art. Preferably, the organic ligand in the MOF material is selected from at least one of 4-methylimidazole, 2-methylimidazole and 2,4-dimethylimidazole.

[0024] According to the present invention, preferably, the MOF material has a layered crystal structure of ZIF-L.

[0025] The ZIF-L layered crystal structure of the MOF material of the present invention is measured by XRD, which can be referred to Figure 2 .from Figure 2 It can be seen that the diffraction peak of the synthetic brick-like MOF corresponds well to the peak position of the ZIF-L of the standard layered crystal structure. With this preferred embodiment, ion adsorption or exchange is faster.

[0026] A second aspect of the present invention provides a method for preparing a MOF material, the method comprising the following steps: (1) reacting an aqueous solution containing a surfactant and an organic ligand with an aqueous solution of a metal source precursor to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The mass dosage ratio of the organic ligand, the metal source precursor and the surfactant is 0.9-1.3:1:0.05-0.4.

[0027] The mass ratio of the organic ligand, the metal source precursor and the surfactant in the present invention is 0.9-1.3:1:0.05-0.4, preferably 1-1.2:1:0.1-0.3. This preferred embodiment can ensure a suitable nucleation rate, and the surfactant can be effectively adsorbed on a specific crystal plane, ultimately forming the brick-like MOF material of the present invention.

[0028] When the number of the surfactants is two or more, the mass amount of the surfactants is the total mass amount of the two or more surfactants.

[0029] According to the present invention, preferably, the surfactant is selected from at least one of polyvinyl pyrrolidone, N-dodecyl pyrrolidone and N-octyl pyrrolidone.

[0030] The present invention has no particular limitation on the molecular weight of the polyvinyl pyrrolidone, and polyvinyl pyrrolidone of various molecular weights in the art can be used. Preferably, the weight average molecular weight of the polyvinyl pyrrolidone is 20,000-40,000 g / mol. This preferred embodiment is more conducive to obtaining the MOF material with the characteristics of the present invention.

[0031] Preferably, the surfactant is polyvinyl pyrrolidone, and N-dodecyl pyrrolidone and / or N-octyl pyrrolidone.

[0032] Preferably, the mass ratio of polyvinyl pyrrolidone to N-dodecyl pyrrolidone and / or N-octyl pyrrolidone is 1:0-0.25, preferably 1:0.05-0.2.

[0033] The inventors of the present invention discovered during the research process that the use of specific types of surfactants in specific proportions is beneficial to controlling the amount and rate of adsorption on specific crystal surfaces, and is beneficial to inhibiting crystal surface growth, thereby obtaining the MOF material with the specific morphology and structure described in the present invention.

[0034] The organic ligand of the present invention can be a conventional choice in the art. Preferably, the organic ligand is selected from at least one of 4-methylimidazole, 2-methylimidazole and 2,4-dimethylimidazole.

[0035] According to the present invention, preferably, the metal source precursor is a soluble salt of a metal source, preferably at least one selected from cobalt acetate, zinc chloride, cobalt nitrate, zinc nitrate, cobalt chloride and zinc acetate. The above substances are conventionally selected in the art and can be obtained commercially.

[0036] In the present invention, the "soluble" means that the compound can be dissolved in a solvent directly or with the help of a co-solvent.

[0037] According to the present invention, preferably, in the aqueous solution containing a surfactant and an organic ligand, the mass amount of the organic ligand is 10-60 mg, preferably 20-40 mg, relative to 1 mL of water.

[0038] According to the present invention, preferably, in the aqueous solution containing a surfactant and an organic ligand, the mass amount of the surfactant is 1-15 mg, preferably 5-10 mg, relative to 1 mL of water.

[0039] According to the present invention, preferably, the concentration of the metal source precursor aqueous solution is 15-50 mg / mL, preferably 20-40 mg / mL.

[0040] The present invention has no particular limitation on the specific preparation process of the organic ligand aqueous solution and the metal source precursor aqueous solution, which can be carried out under ultrasonic or stirring conditions. The present invention has no particular limitation on this.

[0041] According to the present invention, preferably, the reaction conditions of step (1) include: temperature of 20-35°C, preferably 24-28°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C and any value in the range formed by any two of these point values; time of 1-6h, preferably 2-4h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h and any value in the range formed by any two of these point values. By adopting this preferred embodiment, the temperature-induced nucleation rate and the degree of brick-like morphology reaction can be controlled.

[0042] In the present invention, the reaction process in step (1) is the process of crystal growth.

[0043] It should be noted that when the reaction time of step (1) exceeds 6 h, the surface of the layered crystal structure of MOF will be partially hydrolyzed.

[0044] Preferably, the reaction in step (1) is carried out under stirring. This preferred embodiment can effectively promote the uniform nucleation of MOF and help avoid the agglomeration of MOF in the subsequent growth process, so as to obtain the MOF material with the morphology and specific size described in the present invention.

[0045] Preferably, the stirring rate of the reaction in step (1) is 200-600 rpm, preferably 300-500 rpm, for example, 200 rpm, 220 rpm, 240 rpm, 260 rpm, 280 rpm, 300 rpm, 320 rpm, 340 rpm, 360 rpm, 380 rpm, 400 rpm, 420 rpm, 440 rpm, 460 rpm, 480 rpm, 500 rpm, 520 rpm, 540 rpm, 560rpm, 580 rpm, 600 rpm and any value in the range formed by any two of these point values. The use of this preferred embodiment is further conducive to promoting the uniform nucleation of MOF, and is further conducive to avoiding the agglomeration of MOF in the subsequent growth process, so as to obtain the MOF material with the morphology and specific size described in the present invention.

[0046] According to the present invention, preferably, before the reaction in step (1) is carried out, an aqueous solution containing a surfactant and an organic ligand is mixed with an aqueous solution of a metal source precursor.

[0047] According to the present invention, preferably, the mixing is performed under stirring conditions.

[0048] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to specific circumstances, as long as the purpose of uniform mixing can be achieved.

[0049] In the present invention, the mixing time is relatively short, generally only 2-5 minutes, and the mixing time is not included in the reaction time of step (1).

[0050] According to the present invention, preferably, the reaction product of step (1) is separated to obtain a solid product.

[0051] The present invention has no particular limitation on the separation method, which can be carried out using conventional technical means in the art and is not limited herein.

[0052] Preferably, the washing in step (2) comprises: first washing with water and then washing with an organic solvent. This preferred embodiment is conducive to removing the surfactant and avoiding hydrolysis of the MOF surface.

[0053] According to the present invention, preferably, the organic solvent is C 1 -C 6 The alcohol is preferably at least one selected from methanol, ethanol and isopropanol.

[0054] The present invention does not particularly limit the washing conditions of step (2), and the washing can be carried out according to conventional methods in the art, as long as the washing is first performed with water until the supernatant is nearly transparent and the MOF is not hydrolyzed, and then the washing is performed with an organic solvent until the supernatant is nearly transparent.

[0055] The drying of the present invention can be carried out under vacuum, under low pressure, or under normal pressure. Preferably, the drying in step (2) is carried out under vacuum.

[0056] The present invention has no particular limitation on the drying conditions in step (2), and the drying conditions can be carried out according to conventional methods in the art, and the present invention is not limited thereto.

[0057] According to a particularly preferred embodiment of the present invention, a method for preparing a MOF material comprises the following steps: (1) reacting an aqueous solution containing a surfactant and an organic ligand with an aqueous solution of a metal source precursor to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The mass ratio of the organic ligand, the metal source precursor and the surfactant is 1-1.2:1:0.1-0.3; The surfactant is polyvinyl pyrrolidone, and N-dodecyl pyrrolidone and / or N-octyl pyrrolidone; The mass ratio of polyvinyl pyrrolidone to N-dodecyl pyrrolidone and / or N-octyl pyrrolidone is 1:0.05-0.2; The reaction conditions of step (1) include: temperature of 24-28°C and time of 2-4h; The reaction in step (1) is carried out under stirring; The stirring rate of the reaction in step (1) is 300-500 rpm.

[0058] The above preferred embodiment is further advantageous for obtaining the MOF material with a brick-like morphology and a layered crystal structure of the present invention. The MOF material of the present invention has a brick-like morphology and a layered crystal structure, and is applied to the electrolysis of water reaction, which is advantageous for improving the apparent activity of the electrolysis of water reaction.

[0059] The third aspect of the present invention provides an application of the imidazole-based MOF material described in the first aspect or the imidazole-based MOF material prepared by the method described in the second aspect in a water electrolysis reaction.

[0060] The present invention will be described in detail below through examples.

[0061] In the following examples, SEM test: The present invention uses a scanning electron microscope of model Hitachi S-4800, with an operating voltage of 5 kV-20 kV and equipped with energy dispersive X-ray spectroscopy (EDS); XRD test: The present invention adopts an X-ray diffractometer of model XRD-6000 manufactured by Shimadzu of Japan, and the test conditions include: tube voltage 40 kV, tube current 40 mA, Cu target Kα radiation, 2θ scanning range 10°-70°, scanning speed 5° / min; Polyvinyl pyrrolidone is a commercial product of Beijing Inokai Technology Co., Ltd., and has a weight average molecular weight of 40,000 g / mol.

[0062] Example 1 (1) Dissolve an appropriate amount of 2-methylimidazole organic ligand, polyvinyl pyrrolidone surfactant and N-dodecyl pyrrolidone surfactant (the mass ratio of polyvinyl pyrrolidone to N-dodecyl pyrrolidone is 1:0.1) in water and stir to obtain solution A. The organic ligand concentration in solution A is controlled at 32.9 mg / mL and the total surfactant concentration is controlled at 7.5 mg / mL. Dissolve an appropriate amount of cobalt nitrate metal source precursor in water and stir to obtain a cobalt nitrate aqueous solution with a concentration of 29.1 mg / mL. Mix the above solution A and the cobalt nitrate aqueous solution and stir for 3 minutes to obtain solution B. Place the above solution B in a constant temperature environment of 27°C and grow crystals at a stirring rate of 350 rpm for 3 hours to obtain a material containing MOF. The mass ratios of the organic ligand, metal source precursor and total surfactant in solution B in step (1) are listed in Table 1.

[0063] (2) The material containing MOF is centrifuged, washed with water, washed with ethanol, and then vacuum dried to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0064] The SEM image of the MOF material prepared in Example 1 is shown as an example. Figure 1 .from Figure 1 It can be seen that the MOF material has a brick-like morphology.

[0065] The XRD spectrum of the MOF material prepared in Example 1 is shown in FIG. Figure 2 .from Figure 2 It can be seen that the MOF material has a layered crystal structure of ZIF-L.

[0066] Example 2 (1) Dissolve an appropriate amount of 4-methylimidazole organic ligand, polyvinyl pyrrolidone surfactant and N-octyl pyrrolidone surfactant (the mass ratio of polyvinyl pyrrolidone to N-octyl pyrrolidone is 1:0.15) in water and stir to obtain solution A. The organic ligand concentration in solution A is controlled at 38 mg / mL and the total surfactant concentration is controlled at 6 mg / mL. Dissolve an appropriate amount of zinc nitrate metal source precursor in water and stir to obtain a zinc nitrate aqueous solution with a concentration of 34 mg / mL. Mix the above solution A and the zinc nitrate aqueous solution and stir for 2 minutes to obtain solution B. Place the above solution B in a constant temperature environment of 25°C and grow crystals at a stirring rate of 380 rpm for 4 hours to obtain a material containing MOF. The mass ratios of the organic ligand, metal source precursor and total surfactant in step (1) solution B are listed in Table 1.

[0067] (2) The material containing MOF is centrifuged, washed with water, washed with methanol, and then vacuum dried to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0068] The SEM images of the MOF material prepared in Example 2 are Figure 1 Similarly, it is shown that the MOF material has a brick-like morphology.

[0069] The XRD spectrum of the MOF material prepared in Example 2 is Figure 2 similar.

[0070] Example 3 (1) Dissolve an appropriate amount of 2-methylimidazole organic ligand, polyvinyl pyrrolidone surfactant and N-dodecyl pyrrolidone surfactant (the mass ratio of polyvinyl pyrrolidone to N-dodecyl pyrrolidone is 1:0.1) in water and stir to obtain solution A. The organic ligand concentration in solution A is controlled at 32.9 mg / mL and the total surfactant concentration is controlled at 7.5 mg / mL. Dissolve an appropriate amount of cobalt nitrate metal source precursor in water and stir to obtain a cobalt nitrate aqueous solution with a concentration of 29.1 mg / mL. Mix the above solution A and the cobalt nitrate aqueous solution and stir for 3 minutes to obtain solution B. Place the above solution B in a static environment at a constant temperature of 25°C for 4 hours to grow crystals to obtain a material containing MOF. The mass ratios of the organic ligand, metal source precursor and total surfactant in solution B in step (1) are listed in Table 1.

[0071] (2) The material containing MOF is centrifuged, washed with water, washed with ethanol, and then vacuum dried to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0072] SEM images of the MOF material obtained in Example 3 and Figure 1 Similarly, it is shown that the MOF material has a brick-like morphology, but the overall size is increased.

[0073] The XRD spectrum of the MOF material obtained in Example 3 is Figure 2 similar.

[0074] Comparative Example 1 The method of Example 1 was followed, except that an appropriate amount of 2-methylimidazole, polyvinyl pyrrolidone surfactant and N-dodecyl pyrrolidone surfactant were dissolved in methanol and stirred to obtain solution A, in which the organic ligand concentration was controlled at 32.9 mg / mL and the total surfactant concentration was controlled at 7.5 mg / mL. An appropriate amount of cobalt nitrate was dissolved in methanol and stirred to obtain a cobalt nitrate methanol solution with a concentration of 29.1 mg / mL, and finally a MOF material with a typical dodecahedral morphology was obtained. The characterization results of the MOF material are listed in Table 1 below.

[0075] Comparative Example 2 The method of Example 1 was followed, except that an appropriate amount of cobalt nitrate metal source precursor was dissolved in water and stirred to obtain a cobalt nitrate aqueous solution with a concentration of 14.55 mg / mL. At this time, the mass ratio of the organic ligand, metal source precursor and surfactant in step (1) was 2.26:1:0.52 to obtain a MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0076] The SEM image of the MOF material prepared in Comparative Example 2 is shown in Figure 3 .

[0077] Comparative Example 3 (1) Dissolve an appropriate amount of 2-methylimidazole organic ligand, polyvinyl pyrrolidone surfactant and N-dodecyl pyrrolidone surfactant (the mass ratio of polyvinyl pyrrolidone to N-dodecyl pyrrolidone is 1:0.1) in water and stir to obtain solution A. The organic ligand concentration in solution A is controlled at 32.9 mg / mL and the total surfactant concentration is controlled at 7.5 mg / mL. Dissolve an appropriate amount of cobalt nitrate metal source precursor in water and stir to obtain a cobalt nitrate aqueous solution with a concentration of 14.55 mg / mL. Mix the above-obtained solution A and the cobalt nitrate aqueous solution and stir for 3 minutes to obtain solution B. Place the above-mentioned solution B in a static environment at a constant temperature of 27°C for 3 hours to grow crystals to obtain a material containing MOF. The mass ratios of the organic ligand, metal source precursor and total surfactant in solution B in step (1) are listed in Table 1.

[0078] (2) The material containing MOF is centrifuged, washed with water, washed with ethanol, and then vacuum dried to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0079] The SEM image of the MOF material obtained in Comparative Example 3 is shown in Figure 4 .from Figure 4 It can be seen that the MOF material prepared in Comparative Example 3 is in the shape of micro-nano rods, and some irregular nanosheets are attached to the surface.

[0080] Comparative Example 4 The method of Example 1 was followed, except that no surfactant was added, to obtain a MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0081] The SEM image of the MOF material obtained in Comparative Example 4 is shown in Figure 5 .

[0082] Comparative Example 5 (1) Dissolve an appropriate amount of 2-methylimidazole organic ligand in water and stir to obtain an organic ligand solution with a concentration controlled at 32.9 mg / mL. Dissolve an appropriate amount of cobalt nitrate metal source precursor in water and stir to obtain a cobalt nitrate aqueous solution with a concentration of 14.5 mg / mL. Mix the above-obtained organic ligand solution and the cobalt nitrate aqueous solution and stir for 3 minutes to obtain solution B. Place the above solution B at room temperature 25°C and stir at 350 rpm for 3 hours to grow crystals to obtain a material containing MOF. The mass ratio of the organic ligand and the metal source precursor in step (1) solution B is listed in Table 1.

[0083] (2) The material containing MOF is centrifuged, washed with water, and then vacuum dried to obtain MOF material. The characterization results of the MOF material are listed in Table 1 below.

[0084] The SEM image of the MOF material obtained in Comparative Example 5 is shown in Figure 6 .

[0085] Table 1 It can be seen from the results in Table 1 that the preparation method of the present invention is conducive to obtaining the MOF material having a brick-like morphology and a specific layered crystal structure of the present invention.

[0086] Compared with the MOF material of the comparative example, the MOF material provided by the present invention has faster ion adsorption or exchange, and it is convenient to use it as a self-template to subsequently construct a stable brick-shaped hollow structure. It is inferred that the use of the MOF material of the present invention in the electrolysis of water reaction is conducive to improving the apparent activity of the electrolysis of water reaction.

[0087] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An imidazole-based MOF material, characterized in that: The MOF material has a brick-like morphology; the MOF material has a layered crystal structure.

2. The MOF material according to claim 1, wherein The size of the MOF material is (6-16)×(2-5)×(0.6-2.5) μm, preferably (8-15)×(2.5-4.5)×(0.8-2.2) μm; The metal elements in the MOF material are zinc and / or cobalt; The organic ligand in the MOF material is selected from at least one of 4-methylimidazole, 2-methylimidazole and 2,4-dimethylimidazole.

3. The MOF material according to claim 1 or 2, wherein: The MOF material has a layered crystal structure of ZIF-L.

4. A method for preparing a MOF material, the method comprising the following steps: (1) reacting an aqueous solution containing a surfactant and an organic ligand with an aqueous solution of a metal source precursor to obtain a solid product; (2) washing the solid product of step (1) and then drying it; The mass dosage ratio of the organic ligand, the metal source precursor and the surfactant is 0.9-1.3:1:0.05-0.

4.

5. The method according to claim 4, wherein: The mass ratio of the organic ligand, the metal source precursor and the surfactant is 1-1.2:1:0.1-0.3; Preferably, the surfactant is selected from at least one of polyvinyl pyrrolidone, N-dodecyl pyrrolidone and N-octyl pyrrolidone; Preferably, the surfactant is polyvinyl pyrrolidone, and N-dodecyl pyrrolidone and / or N-octyl pyrrolidone; Preferably, the mass ratio of polyvinyl pyrrolidone to N-dodecyl pyrrolidone and / or N-octyl pyrrolidone is 1:0-0.25, preferably 1:0.05-0.

2.

6. The method according to claim 4, wherein: The organic ligand is selected from at least one of 4-methylimidazole, 2-methylimidazole and 2,4-dimethylimidazole; Preferably, the metal source precursor is a soluble salt of a metal source, preferably at least one selected from the group consisting of cobalt acetate, zinc chloride, cobalt nitrate, zinc nitrate, cobalt chloride and zinc acetate.

7. The method according to claim 4, wherein: In the aqueous solution containing a surfactant and an organic ligand, the mass amount of the organic ligand is 10-60 mg, preferably 20-40 mg, relative to 1 mL of water; Preferably, in the aqueous solution containing a surfactant and an organic ligand, the mass amount of the surfactant is 1-15 mg, preferably 5-10 mg, relative to 1 mL of water; Preferably, the concentration of the metal source precursor aqueous solution is 15-50 mg / mL, preferably 20-40 mg / mL.

8. The method according to any one of claims 4 to 7, wherein: The reaction conditions of step (1) include: temperature of 20-35°C, preferably 24-28°C; time of 1-6h, preferably 2-4h; Preferably, the reaction in step (1) is carried out under stirring; Preferably, the stirring rate of the reaction in step (1) is 200-600 rpm, preferably 300-500 rpm.

9. The method according to any one of claims 4 to 8, wherein: The washing in step (2) comprises: first washing with water and then washing with an organic solvent; Preferably, the organic solvent is selected from at least one of methanol, ethanol and isopropanol.

10. Use of the imidazole-based MOF material according to any one of claims 1 to 3 or the imidazole-based MOF material obtained by the method according to any one of claims 4 to 9 in a water electrolysis reaction.

Citation Information

Patent Citations

  • Metal-organic framework hydrogen storage material as well as preparation method and application thereof

    CN114479094A

  • Preparation method of MOF-303

    CN115449087A